COMPARISON OF THE SPATIO-TEMPORAL PARAMETERS OF WALKING AT ORDINARY, GIVEN DIMINISHED RATES AND AT WALKING WITH ADDITIONAL COGNITIVE LOADING IN PERSONS OF YOUTH AGE - Bogomaz, О.V. (World of Medicine and Biology, 2014)
The aim of the study was to compare the differences of the spatio-temporal parameters of the step cycle of the ordinary walking, walking with given diminished rate (after the signal of metronome) as well as walking with additional cognitive task in persons of youth age. It was set that at walking with given diminished rate the subjects overcame the mat distance by shorter and more prolonged steps, than at walking with additional cognitive task. Maintenance of equilibrium at walking with given diminished rate and at walking with additional cognitive task is realized by the constancy of the support base width and reorganization of the step cycle in the side of increasing the part of the contact time of foot with a floor and diminishing the part of the swing time. At walking with additional cognitive task, unlike walking with given diminished rate, indices of the spatial and temporal asymmetries appeared considerably more.
Keywords: spatio-temporal parameters of walking; boys; girls